The normal and pathological speech (Continued) - Espejo, Luis D. (1919)
All being organized is the product of two factors: heredity and education. By inheritance we are closely linked to the history of life, from the protozoan whose origin placed at sea fantasy Lucrecio and scientific research, to our parents. Through education, experience and continuing the slow action of the environment, be it cosmic energy, physical and intellectual culture or civilization.